Space radiation dose and particle flux distribution from low Earth to Moon orbits - Semkova, Jordanka; Dachev, Tsvetan (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The space radiation is a very important component of the space weather and affects both the space crew and electronic devices in space flights. The Bulgarian scientists together with number of international partners for more than 20 years conduct research of the ionizing radiation distribution from the Earth surface to the Moon orbit. In this paper we present some results for space radiation doses observed during number of experiments on the Mir manned space station, International Space Station, on unmanned satellites Foton-M2, Foton-M3 around the Earth and on Chandrayan-1 satellite around the Moon. Discussed is the contribution of the galactic cosmic rays and trapped radiation to the particle fluxes and absorbed doses. Key words: Ionizing Space radiation, Galactic cosmic rays, Solar cosmic rays, Earth radiation belts, Space radiation measurements, Low Earth orbit, Moon orbit.